﻿Method development and validation of cabozantinib by LC-MS/MS - Punna Venkateshwarlu; Mehul M. Patel (Pensoft Publishers, 2022)
The objective of this method is to be simple, precise, and economical performed by LC-MS/MS instrument. The mass spectrometric determination was performed using electrospray ionization in the positive mode with multiple reaction monitoring (MRM) mode and precursor to product ion transition to product ion of m/z 502.2 > 323 for cabozantinib. The effective separation of cabozantinib was achieved X-Bridge (2.1 mm × 100 mm, 3.5 µ) column and the mobile phase composition is 0.2% formic acid: acetonitrile (40:60 v/v), pumped at 0.12 ml/min flow rate. The Rt of cabozantinib was found to be 1.34 minutes. The LOD and LOQ were found at 1.5 ng/ml and 5 ng/ml concentrations and linearity concentrations were in a range of 5 ng/ml to 75 ng/ml with a regression correlation coefficient of 0.999. The % RSD value of accuracy was observed at 1.2-2.0. The marketed formulation assay was found to be 99.82%. The developed method and validation parameters were accepted as per USFDA guidelines.